CO2 Emission Factors and Carbon Losses for Off-Road Mining Trucks - Carvalho, João Andrade de[UNESP]; Castro, André de; Brasil, Gutemberg Hespanha; Souza, Paulo Antonio de; Mendiburu, Andrés Z. (MDPI, 2022)
There are myriad questions that remain to be answered in greenhouse gas (GHG) emissions trading. This article addresses carbon dioxide (CO2) emission factors and carbon losses from heavy equipment that is used to transport ores. Differences occurred between the Intergovernmental Panel for Climate Change (IPCC) emission factor and those that were obtained by considering incomplete combustion and on-site exhaust concentration measurements. Emissions from four off-road vehicles were analyzed. They operated at idle (loading, unloading, and queuing) and in motion (front and rear, loaded and unloaded). The results show that the average CO2 emission factors can be as low as 64.8% of the IPCC standard value for diesel fuel. On the other hand, carbon losses can be up to 33.5% and energy losses up to 25.5%. To the best of the authors’ knowledge, the method that was developed here is innovative, simple, useful, and easily applicable in determining CO2 emission factors and fuel losses for heavy machinery.
Keywords: carbon losses; CO2 emission rates; heavy duty equipment